2018
DOI: 10.1016/j.infsof.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

What software reuse benefits have been transferred to the industry? A systematic mapping study

Abstract: Context: The term software reuse was first used in 1968 at the NATO conference. Since then, work in the scientific literature have stated that the application of software reuse offers benefits such as increase in quality and productivity. Nonetheless, in spite of many publications reporting software reuse experiences, evidence that such benefits having reached industrial settings is scarce. Objective: To identify and classify the benefits transferred to real-world settings by the application of software reuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 64 publications
3
11
0
Order By: Relevance
“…Similar benefits of software reuse in industrial contexts are reported in the literature [14,2]. The most reported benefits are increased quality [2], increased productivity [14,2], reduced development cost and time and a lower defect rate [2]. While reflecting on 15 years of reuse, we observe these same benefits throughout our different prototypes.…”
Section: Discussionsupporting
confidence: 85%
“…Similar benefits of software reuse in industrial contexts are reported in the literature [14,2]. The most reported benefits are increased quality [2], increased productivity [14,2], reduced development cost and time and a lower defect rate [2]. While reflecting on 15 years of reuse, we observe these same benefits throughout our different prototypes.…”
Section: Discussionsupporting
confidence: 85%
“…Similar benefits of software reuse in industrial contexts are reported in the literature [16,2]. The most reported benefits are increased quality [2], increased productivity [16,2], reduced development cost and time and a lower defect rate [2]. While reflecting on 15 years of reuse, we observe these same benefits throughout our different prototypes.…”
Section: Benefits Of Reuse For Evolutionary Prototypingsupporting
confidence: 85%
“…By acknowledging the tremendous relevance of technical debt in software development industries, the TD community is striving to produce methods and tools for TD Management (TDM) that would reduce the amount of TD in the software, by either preventing the accumulation of additional TD, or by removing the existing one ( Arvanitou et al, 2019 ). To this end, the roots of TD have been extensively studied Mo et al, According to Barros-Justo et al (2018) , research efforts should focus on the use of quality models for testing the actual impact of reuse benefits, with maintainability appointed as the most important one, while linking them to specific practices. In this direction Mikkonen and Taivalsari (2019) stress that the revival of software reuse, due to the enormous amount of freely available source code on the web, poses new challenges to the software engineering community related to the systematic analysis of the compatibility and the properties of popular open source components.…”
Section: Introductionmentioning
confidence: 99%